Awareness of the rights of the children among health professionals working at children hospital. - Shrestha, Ishwari Devi (2005)
ABSTRACT: The study entitled awareness of the rights of the children was undertaken among the health professionals working in Children Hospital, Kathmandu. The objective was to find out the awareness of the rights of the children among health professional's working in children hospital. A simple descriptive research design was applied for the sample size of 100 using non probability purposive sampling technique. A self administered semi structure questionnaire was used as a research tools for data collection. Finding reveals that the respondents were 40% PGMD, 30% MBBS and 13% FRCP/SR/PHD/, 17% DMRD/DHH, 68% PCL Nurses, 26% Bachelor Nurses, 3% Master Nurses and 3% Auxiliary Nurses working in Children Hospital. 90% respondents were aware in general children's rights however 50% were unaware in detail components of children's rights (survival rights, Protection rights, developmental rights and participation rights). Only 3% respondents had obtained formal training about chlidren's rights. They were aware about children's rights from the mass medias. Conclusion was mad that respondents were remarked in fulfilling additional children's rights activities in hospital, which increase children's moral, quality and consiciousness care, speedy recovery, hospital image and professional images. The recommendations were orientation of children's right is necessary, formal training on children's rights to the health professionals and information to parents and children about rights of the child.